Politik Hukum Tindak Pidana Perzinahan Dalam Kitab Undang-Undang Hukum Pidana Dan Dalam Rancangan Kitab Undang-Undang Hukum Pidana - Ndaru Satrio (Fakultas Syariah dan Ekonomi Islam, 2021)
Social, cultural, and religious values view that adultery in all its forms, whether committed by people who are married or who are not married, is a very disgraceful act, Political developments adultery criminal laws in the Book of the Criminal Justice Act and the Draft Code of Criminal Law, a. According RKUHP term used to refer to the term fornication is permukahan, b. Based on Article 483 paragraph (1) the concept of KUHP perpetrators of permukahan crimes are threatened with a maximum imprisonment of five years, c. the concept of KUHP is that the concept does not distinguish between married and unmarried perpetrators. d. RKUHP does not require any more for man’s subject to Article 27 BW (Civil Code).